1987
DOI: 10.1128/aac.31.12.1904
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatography measurement of antimicrobial concentrations in polymorphonuclear leukocytes

Abstract: High-performance liquid chromatography was used to determine the penetration of 19 antimicrobial agents into human polymorphonuclear leukocytes. The ratios of the intracellular concentration to the extraceHlular concentration of ampicillin, piperacillin, cefazolin, ceftizoxime, cefpimizole, and ceftazidime were all less than 0.6. Lincomycin showed a high intracellular-to-extraceliular ratio (3.0), while clindamycin achieved a ratio of 15.5, which was the highest ratio of all of the 19 tested antibiotics. Ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 18 publications
7
84
0
Order By: Relevance
“…The injected sample flowed with the mobile phase through the separation column and to the mixer. At the mixer, the separated sample solution was mixed with bipyridine complex of ruthenium ((Ru(bpy) 3 ) 3+ ) solution, which was prepared by oxidation of (Ru(bpy) 3 ) 2+ . The reaction between (Ru(bpy) 3 ) 3+ and compounds with the alicyclic tertiary amine structure produced chemiluminescence, the intensity of which was measured and digitized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The injected sample flowed with the mobile phase through the separation column and to the mixer. At the mixer, the separated sample solution was mixed with bipyridine complex of ruthenium ((Ru(bpy) 3 ) 3+ ) solution, which was prepared by oxidation of (Ru(bpy) 3 ) 2+ . The reaction between (Ru(bpy) 3 ) 3+ and compounds with the alicyclic tertiary amine structure produced chemiluminescence, the intensity of which was measured and digitized.…”
Section: Resultsmentioning
confidence: 99%
“…10,11) Thus, in the present study, we examined whether LC using a tris(2,2 -bipyridine) ruthenium (III) chemiluminescence detection system would be suitable for the quantitative analysis of macrolide antibiotics in cells. The ruthenium complex (Ru(bpy) 3 ) 3+ has specific binding activity to the alicyclic tertiary amine structure found in macrolide antibiotics, and is currently used for chemiluminescence analysis. [10][11][12][13][14][15] Clarithromycin (CAM) was used in the present study as the representative macrolide antibiotic since it has been widely used for a long time in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…26) CLDM/LCM enhanced the cytoplasmic function of polymorphonuclear leukocytes, accelerated phagocytosis and promoted antibody production by lymphocytes. [27][28][29] It is also reported that subminimal inhibitory concentrations of CLDM influenced bacterial viability, toxin production, and host response. 30) As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%